1994
DOI: 10.1203/00006450-199406000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Bifidobacterium bifidum in Mediating the Clinical Course of Murine Rotavirus Diarrhea

Abstract: ABSTRACT. Human Bifidobacterium sp strain bifidum (B. bifidum) was administered to BALB/c lactating mice (n = 58) and their litters (n = 327 pups) to evaluate the ingested strain's adherent properties and ability to inhibit murine rotavirus (MRV) infection. ELISA and anaerobic bacteriologic techniques were used to measure MRV shedding and colonization of Bifidobacterium in the small intestine. The biologic mechanisms underlying the interactions between the normal microbial flora and infectious challenge by ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
1
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 6 publications
1
30
1
1
Order By: Relevance
“…In comparison, the viral shedding continued to increase gradually until 7 d PI, the last time point tested in all infected groups. This virus shedding pattern was different from that observed in a previous study with murine rotavirus (MRV) (17), in which the viral shedding in stool declined on d 7 PI in both bifidobacteria and nonbifidobacteria-treated, MRVinfected mice. One possible reason for this difference could be the fact that RRV has liver tropism (19).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In comparison, the viral shedding continued to increase gradually until 7 d PI, the last time point tested in all infected groups. This virus shedding pattern was different from that observed in a previous study with murine rotavirus (MRV) (17), in which the viral shedding in stool declined on d 7 PI in both bifidobacteria and nonbifidobacteria-treated, MRVinfected mice. One possible reason for this difference could be the fact that RRV has liver tropism (19).…”
Section: Discussioncontrasting
confidence: 99%
“…Although bifidobacteria were not routinely isolated in samples from treated mice in these experiments, we cannot summarily conclude that the organisms were not present in the gut, inasmuch as our previous research has shown that B. bifidum can successfully colonize the mouse intestine (17). In that study, 80% of minced small intestine samples from B. bifidumtreated mice were culture positive for B. bifidum, although the ingested strain was not isolated from the intestines of mice challenged with MRV alone or from saline control animals.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In conclusion, inhibitory effect of cPGN , live bifidobacterial cell, and their mixture in all concentrations on rotavirus infection was superior when cPGN and live bifidobacterial cell were used simultaneously. Probiotic lactic acid bacteria was well known to protect infection as they competitively acted against adherence to adherent site in epithelial cell (4,17 …”
Section: Variation Of Adherence Ability By Crude Peptidoglycan Dependmentioning
confidence: 99%
“…2) Some Bifidobacterium species are widely used for the preparation of fermented milk products all over the world, and are believed to have health-promoting properties for their host, involving enhancement of immune response, 3) an inhibitory effect for carcinogenesis, 4) protection of the host against viral infection, 5,6) and possible production of antibacterial substances. 7) Furthermore, Bifidobacterial plasmids are expected to be vectors for probiotics and for oral vaccine against infectious diseases.…”
mentioning
confidence: 99%